Waḥdat al-Wujūd dan Deus sive Natura: Implikasi Filosofis bagi Kesadaran Lingkungan - Rohmadin, Muhammad; Naupal, Naupal (Refleksi, 2024)
Awareness of climate change, pollution, and environmental degradation has increased in recent decades, triggering global movements to protect ecosystems and ensure the sustainability of natural resources. This article examines the philosophical views of Ibn Arabī and Spinoza on the relationship between God and the universe and their implications for environmental awareness. In Ibn ‘Arabī point of view nature as a manifestation of God, thus preserving nature is an act of worship and respect towards God. In Baruch Spinoza point of view nature is an expression of the eternal God, providing a strong ethical foundation for environmental preservation. In Indonesia, an integrating traditional cultural and spiritual values with modern approaches can create holistic strategies for protecting the environment and supporting sustainable development. This article aims to enhance environmental awareness by combining scientific, moral, and spiritual perspectives, and inspiring sustainable actions in safeguarding nature as part of humanity’s moral and spiritual responsibility.